Simple models for managing complex social–ecological systems: The Landscape Futures Analysis Tool (LFAT). (January 2015) - Summers, David M.; Bryan, Brett A.; Meyer, Wayne S.; Lyle, Greg; Wells, Sam; McLean, Josie; Moon, Travis; van Gaans, Greg; Siebentritt, Mark
Abstract: Integrated modelling and assessment can facilitate exploration of complex social–ecological interactions and quantify trade-offs in regional policy, planning, and management options. However, there have been challenges in its acceptance and adoption for supporting decisions. Here we overcome this implementation gap through the development of an interactive online tool called the Landscape Futures Analysis Tool (LFAT) (http://www.lfat.org.au/ ). Identifying four high priority regional management issues; agricultural production, carbon sequestration, biodiversity conservation and weed management, we developed a series of simple models to explore them through a range of environmental and economic scenarios including climate change, carbon price, agricultural commodity price, and production costs. These models were implemented within the LFAT to allow users to select, query and explore combinations of key variables and examine their impact on each of the management issues through a range of interactive maps and summary statistics. Highlights: We developed simple models to explore 4 key regional land management issues. Models were implemented in the interactive, online Landscape Futures Analysis Tool. Users can explore key uncertainties in productivity, prices, costs and global change. LFAT provides interactive maps and summary statistics to inform planning. LFAT helps bridge the implementation gap in land management and planning